3.
a) x-3=-2
-2-3=-2
-2-3≠-2
1-3=-2
-2=-2
x=1
Liczba 1 spełnia równanie.
b) 3x-8=1
3*(-2)-8=1
-6-8≠1
3*1-8=1
3-8≠1
3*3-8=1
9-8=1
x=3
Liczba 3 spełnia równanie.
c) 5x+3=8
5*(-2)+3=8
-10+3≠8
5*1+3=8
5+3=8
x=1
Liczba 1 spełnia równanie.
d) 5=2x-1
5=2*(-2)-1
5≠(-5)
5=2*1-1
5≠2-1
5=2*3-1
5=6-1
x=3
Liczba 3 spełnia równanie.
e) -5=2x-1
-5=2*(-2)-1-5=-4-1
x=-2
Liczba -2 spełnia równanie.
f) -2x-3=-5
-2*(-2)-3=-5
4-4≠-5
-2*1-3=-5
-2-3=-5
x=1
Liczba 1 spełnia równanie.
g) 3x+8=-x
3*(-2)+8=-(-2)
-6+8=2
x=-2
Liczba -2 spełnia równanie.
4.
a) 5*4+7=20+7=27
5x+7=27
b) 6x- ...... =5
6*4- ...... =5
24- ..... =5
24-19=5
6x-19=5
c) 10=3x- ......
10=3*4- ......
10=12- .....
10=12-2
10=3x-2
d) 3= .... +2x
3= .... +2*4
3= .... +8
3=(-5)+8
3=-5+2x